The impact of macroprudential policy and political institutions on bank credit risk in Ethiopia: A dynamic ordinary least squares analysis - Mohammed Adem (Cogent Business & Management, 2023)
Credit risk in financial institutions has been widely debated among experts and legislators as a substantial risk to the financial industry's health. In addition to examining bank-specific and macroeconomic reasons, the study examines the impacts of political institutions and macroprudential regulations on credit risk in Ethiopia. Using panel data from 2011-2019 and employing dynamic ordinary least squares, the findings imply that political institutions have significant positive links to credit risk. It also found that macroprudential policy helps to control bank risk and reduce exposure in the banking industry. The results indicate that banks with larger sizes and profitability have less credit risk. The findings support the'skimping' and "dark side of diversification" hypotheses; retaining a higher loan-to-asset ratio, cost-effectiveness, and diversity of the banking commercial model reduces credit quality by promoting credit risk. A higher inflation rate reduces credit risk by increasing borrowers' potential to service their debts when lending rates are fixed. GDP and the exchange rate have little influence on credit risk. The outcomes of this study provide significant implications for authorities and bankers in developing countries such as Ethiopia in the understanding of credit risk-determining elements to implement prudential rules and remedial management policies.
Keywords: C33; C58; G20; G21; 650; Credit risk; Dynamic ordinary least square; Ethiopia; Macroprudential policy; Political institution